Radiation Damage on SiPM for High Energy Physics Experiments in space missions - Guerrisi Celeste; Ruzzarin Maria Stella; Acerbi Fabio; Bissaldi Elisabetta; Di Venere Leonardo; Gargano Fabio; Giordano Francesco; Gola Alberto; Loporchio Serena; Merzi Stefano; Moretti Elena; Palù Giovanni (EPJ Web of Conferences)
Silicon photomultipliers (SiPMs) are a popular choice for various applications, especially in astroparticle physics. These devices are coupled with organic or inorganic scintillators, allowing them to detect scintillation light and Cherenkov light. They are particularly promising for space missions because of their compact size, low operating bias, and non sensitivity to magnetic fields. We studied the effects of proton irradiation at fluences up to 1 × 1011p/cm2 on FBK’s NUV-HD-lowCT SiPMs with 40 μm and 15 μm cell pitches. Proton-induced bulk damage increased the dark count rate (DCR) and dark current, with no significant changes in the breakdown voltage. These results align with previous studies on radiation effects in SiPMs and provide insights to mitigate performance degradation in space applications.